RNA interference suppression of AGAMOUS and SEEDSTICK alters floral organ identity and impairs floral organ determinacy, ovule differentiation, and seed‐hair development in Populus - Lu, Haiwei (John Wiley and Sons Inc., 2019)

(untitled) (New Phytol)
The role of the floral homeotic gene AGAMOUS (AG) and its close homologues in development of anemophilous, unisexual catkins has not previously been studied. We transformed two RNA interference (RNAi) constructs, PTG and its matrix‐attachment‐region flanked version MPG, into the early‐flowering female poplar clone 6K10 (Populus alba) to suppress the expression of its two duplicate AG orthologues. By early 2018, six out of 22 flowering PTG events and 11 out of 12 flowering MPG events showed modified floral phenotypes in a field trial in Oregon, USA. Flowers in catkins from modified events had ‘carpel‐inside‐carpel’ phenotypes. Complete disruption of seed production was observed in seven events, and sterile anther‐like organs in 10 events. Events with strong co‐suppression of both the two AG and two SEEDSTICK (STK) paralogues lacked both seeds and associated seed hairs. Alterations in all of the modified floral phenotypes were stable over 4 yr of study. Trees from floral‐modified events did not differ significantly (P < 0.05) from nonmodified transgenic or nontransgenic controls in biomass growth or leaf morphology. AG and STK genes show strong conservation of gene function during poplar catkin development and are promising targets for genetic containment of exotic or genetically engineered trees.